Intention for Hepatitis B Vaccination among Male-to-female Transgenders in Bandung - Khiruddin, Ain Izzati; Afriandi, Irvan; Aznur, Laili; Setiawati, Elsa Pudji (Althea Medical Journal, 2015)
Background: Hepatitis B is still an alarming global disease nowadays. The majority of transmission is byÂ sexual activity during adulthood and male-to-female transgender is a high risk group. Despite protectiveÂ vaccine is available, vaccination coverage among these high risk groups remained low. This study aimedÂ to compare the differences in attitude, subjective norms, and perceived behavioral control between theÂ intended group and unintended group for hepatitis B vaccination among male-to-female transgenders inÂ Bandung.Methods: A Cross-sectional study was conducted during SeptemberâNovember 2012 to 100 male-to-femaleÂ transgenders residing in Bandung. Thirteen Likert scales validated questionnaires were used to compareÂ the attitude, subjective norms and perceived behavioral control by their intention of hepatitis B vaccinationÂ (Theory of Plan Behavior/TPB). the respondents were recruited by the help of Srikandi Pasundan, thatÂ actively works in the issues of transgender. The inclusion criterias were they regard themselves as waria,Â consistent as a transgender for at least six months, residing in Bandung, and sexually active within sixÂ months. Independent variables consist of demographic characteristics and TPB construct variables. MannÂ Whitney Test was used to analyze the data.Results: Among 75% of the unvaccinated respondents, majority (70.7%) have the intention to get hepatitisÂ B vaccination. Mann Whitney analysis showed that there is a difference of attitude between the intendedÂ group and unintended group for hepatitis B vaccination, while there are no differences by their intention forÂ subjective norms and perceived behavioral control.Conclusion: The attitude influenced vaccination intention among male-to-female transgenders in Bandung.Â [AMJ.2015;2(1):253â61]